(untitled) (Comprehensive Journal of Science, 2026)
This study aims to investigate the nature of the causal relationship between strategic planning (with its five dimensions: vision and mission, strategic goals and values, environmental analysis, projects and operational plans, and monitoring and evaluation) and organizational performance at the University of Zawia, within the context of unstable environmental transformations witnessed by Libyan educational institutions. The study adopted the descriptive analytical approach, and utilized a structured questionnaire as the primary tool for data collection from a purposive-random sample consisting of (80) academic and administrative staff members. Data were subjected to statistical analysis using SPSS v.28, through reliability tests (Cronbach’s Alpha), Pearson Correlation coefficient, and Multiple Regression Analysis. The results revealed the existence of a positive, strong, and statistically significant correlation (at a significance level of α≤0.01) between strategic planning and organizational performance (r=0.74, p<0.01). Regression analysis further indicated that strategic planning explains (54.8%) of the total variance in organizational performance (R²=0.548). The dimension of (projects and operational plans) emerged as the strongest predictor (β=0.328, p<0.001), followed by (monitoring and evaluation) (β=0.285), while the dimension of (vision and mission) was the least influential (β=0.142). The study recommends transitioning from a "formulation culture" to an "implementation culture" by building an integrated institutional system for periodic monitoring (KPIs), translating strategic plans into flexible operational budgets, and adopting artificial intelligence techniques for monitoring strategic performance.